"Siri, Show Me Scary Images of AI": Effects of Text-Based Frames and Visuals on Support for Artificial Intelligence. Issue 3 (June 2021) - Bingaman, James; Brewer, Paul R.; Paintsil, Ashley; Wilson, David C.
This research note examines how framing influences attitudes toward artificial intelligence (AI). It uses an experiment embedded in a nationally representative online survey to test the effects of text-based frames and visuals on opinion about developing, funding, and banning AI. Participants exposed to a "social progress" frame reported greater support for AI than those exposed to a "Pandora's box" frame. Images (virtual assistants, personal robots, menacing movie AIs, or none) did not influence opinion by themselves but interacted with textual frames to do so. The results extend our understanding of framing effects on public attitudes toward emerging technologies.